Comparative study of post placental cut insertion following vaginal and caesarean delivery - Lall, Jasmine; Nagar, Oby (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The IUCD is a safe and effective contraceptive option for postpartum women who wish to either space or limit subsequent births. Methods: In a hospital based prospective observational, study we compared outcome of post placental IUCD in vaginal and caesarean delivery groups. Results: We found that expulsion rate is significantly higher in vaginal group (10%) as compared to caesarean delivery (2%) group at 3 months of follow up. Excessive bleeding is mostly commonly found complication (18% in both groups at 6weeks of follow up). Conclusions: Women who receive PPIUCD show a high level of satisfaction with this choice of contraception, and the rates of expulsion were low enough such that the benefits of contraceptive protection outweigh the potential inconvenience of needing to return for care for that subset of women.